THE CARRY TRADE ON THE EURO AND THE EUROPEAN STOCK MARKET - PARLAPIANO , Fabio (Journal of Advanced Studies in Finance; Vol 5 No 1 (2014): JASF Volume V, Issue 1(9), Summer, 2014, 2014)
We analyze the influence of carry trades involving the Euro on the Eurozone stock market, modeling returns as dependent on macroeconomic risk factors and speculative positions. The latter are measured by the net open futures positions recorded on the CME. While correlated with the standard carry-to-risk and forward discount proxies, net open positions have the considerable advantage of being directly observable. The results show that long future positions on the Euro rise contemporaneously with the positive returns in the stock market, supporting the hypothesis that speculative capital flows may inflate or stress the market price of financial assets.